2013
DOI: 10.1080/10410236.2013.786278
|View full text |Cite
|
Sign up to set email alerts
|

Older Adults’ Evaluations of Middle-Aged Children’s Attempts to Initiate Discussion of Care Needs

Abstract: We explored how older adults evaluated the strategies used by an adult child to initiate discussion of future care needs, and subsequently, whether these judgments affected older adults' willingness to engage in discussions about eldercare if approached in a similar fashion by one of their own children. One hundred and thirty older adults were randomly assigned to read one of four scripts depicting efforts by a middle-aged daughter to raise the topic of future care needs with her mother by implementing a varie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…First, since the adult child feels that the care is never sufficient, feelings of guilt, burn out and depression may arise (Gonyea et al 2008 ; Springate and Tremont 2014 ; Madsen and Birkelund 2013 ; Roach et al 2013 ). Second, if the parent becomes physically or mentally unable to maintain the parental role from the past, the adult child may feel anxious and incapable of providing adequate support—which, in turn, may affect the parent’s ability to accept the care (Fowler et al 2014 ). Thus, filial maturity requires successful achievement of both distancing and comprehending.…”
Section: Introductionmentioning
confidence: 99%
“…First, since the adult child feels that the care is never sufficient, feelings of guilt, burn out and depression may arise (Gonyea et al 2008 ; Springate and Tremont 2014 ; Madsen and Birkelund 2013 ; Roach et al 2013 ). Second, if the parent becomes physically or mentally unable to maintain the parental role from the past, the adult child may feel anxious and incapable of providing adequate support—which, in turn, may affect the parent’s ability to accept the care (Fowler et al 2014 ). Thus, filial maturity requires successful achievement of both distancing and comprehending.…”
Section: Introductionmentioning
confidence: 99%
“…Messages generated from this study were used to create scripts for the next phase of the larger investigation in which we sought to test whether complex messages (involving the manipulation of positive and negative face-threatening and face-supporting messages) affected older adults’ willingness to engage in discussions about future care needs (Fowler et al, in press). Ultimately, recognizing that low levels of communication efficacy are a profound impediment to adult children engaging their parents in a discussion of future care needs (Fowler & Afifi, 2011), we hope that by assessing how parents react to certain kinds of politeness messages, we may be in a position to help adult children construct their own messages, and that by being able to provide a detailed account of the sorts of remarks that comprise effective openers, we may be able to enhance feelings of communication efficacy.…”
Section: Resultsmentioning
confidence: 99%
“…Ultimately, recognizing that low levels of communication efficacy are a profound impediment to adult children engaging their parents in a discussion of future care needs (Fowler & Afifi, 2011), we hope that by assessing how parents react to certain kinds of politeness messages, we may be in a position to help adult children construct their own messages, and that by being able to provide a detailed account of the sorts of remarks that comprise effective openers, we may be able to enhance feelings of communication efficacy. Consequently, the next step is to design and implement an evaluative intervention study in which adult children use strategies identified here and in Fowler et al (in press) to open conversations with aging parents and to assess the effectiveness and outcomes of those intergenerational discussions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When informal caregivers feel that the care is not sufficient, this may lead to feelings of burn out, depression, and guilt. (Almberg, Grafström, & Winblad, 1997, Collins & Jones, 1997Donaldson, Tarrier, & Burns, 1998;Edwards & Scheetz, 2002;Ekwall & Hallberg, 2007;Gonyea, Paris, & De Saxe Zerden, 2008;Madsen & Birkelund, 2013;Roach, Laidlaw, Gillanders & Quinn, 2013;Springate & Tremont, 2014) In particular, cognitive problems of the care recipient are related to an increased complexity of the care and increased burden of the informal caregiver (Fowler, Fisher, & Pitts, 2014;Nordtug & Holen, 2011;Sequiera, 2013;Wenzel & Poynter, 2014). Apart from stress, problems in the social and relational domain occur, (Feinberg & Whitlatch, 2002), especially when the care recipient has cognitive problems (Harris, 2013;Luchetti et al, 2009).…”
Section: Introductionmentioning
confidence: 99%